THE INFLUENCE OF DOCUMENTARY VIDEO TOWARD STUDENTS ABILITY IN WRITING DESCRIPTIVE TEXT ELEVENTH GRADE AT SENIOR HIGH SCHOOL 1 KOTA GAJAH ACADEMIC YEAR 2020/2021 - Prayoga, Muhtar Hadi; Faliyanti, Eva; Thresia, Fenny (Journal of English Education and Enterpreneurship (JEEP), 2021)
The Influence of Documentary Video Toward Students Ability in Writing Descriptive Text Eleventh Grade At Senior High School 1 Kota Gajah Academic Year 2020/202. The urgency of technology integration has arisen due to the current pandemic break. With a sudden shift from conventional learning to virtual learning, less proper preparation for utilizing the technology integration may occur. The present study aimed at writing ability using documentary video as a medium. By applying experimental research with observation case study design in Senior High School 1 Kota Gajah, this study gained the data through questionnaires, writing tasks, and an interview. Brata in Annisa's (2019) documentary video is a form of audiovisual product that tells a daily phenomenon. This phenomenon deserves to be a reflection of the audience. The results of the study proved that the use of documentary videos as a medium in improving students' writing ability of descriptive texts, In the pre-test, the average score of the experimental group and the control group are 53.26 and 56.77. From the score of the two groups, the result shows that the experimental group is lowest than that of the control one. However, the result of the post-test of the experimental group is higher than that of the control group; they are 87.49 for the experimental group and 71.20 for the control group. There was a significant difference in student’s English writing skills that learned writing by using Documentary video and conventional media.